Why Do You Care? Exploring The Experiences of Health Care Providers Supporting Patients with Dementia in Primary Care Memory Clinics - Sheiban, Linda (University of Waterloo, 2014)
Background: Alzheimer’s disease and related dementias (ADRD) are often improperly or under-diagnosed in primary care; yet, it is expected that community-based care will be an increasingly important source of support for ADRD patients. In Ontario, primary care has continued to expand its services to include health team models, such as family health teams (FHTs) to provide multidisciplinary collaborative care for patients. Within such teams, memory clinic teams have also been implemented, which are clinic days set up typically once or twice a month to provide interprofessional collaborative care specifically for ADRD patients by trained health care providers (HCPs). Objective: Little is known about the experience of HCPs who work in primary care memory clinic team settings to provide care for ADRD patients. This study explored these experiences. Specifically, questions were asked around the rewards, challenges and motivations with working in the memory clinic structure and providing support to ADRD patients. Methods: A phenomenological approach was used. One-on-one semi-structured interviews were completed with 12 interprofessional team members in two primary care memory clinic teams. Interviews were transcribed and analyzed using Colaizzi’s (1978) method of analysis. Results: Overall, seven subthemes were found which describe the HCP experience. The first two subthemes describe experiencing the journey with the patient and caregiver. HCPs want to support patients while maintaining the patient’s dignity. They also balance emotional dilemmas with responsibilities. The next two subthemes describe experiencing the journey with the team. HCPs feel valued and connected to their team members. The memory clinic structure offers unique care provider experiences. Lastly, three subthemes were found which describe the personal and professional rewards of the experience. HCPs found thrilling complexities within the patient population in the memory clinic and that working in the clinic they are able to experience ongoing learning opportunities. HCPs also described that the memory clinic offers personal and professional fulfillment. Discussion: HCPs described an overall positive experience working in the memory clinic to support ADRD patients. HCPs take pride in being able to support patients and caregivers. Knowing that they are making a difference and doing good work are motivations to continue to work with complex populations, such as ADRD patients. HCPs enjoy working in close proximity to one another, respect their team members, and enjoy learning from each other. Team members motivate each other to stay and work with the ADRD population in primary care memory clinics. HCPs reap many rewards associated with working in a “tight-knit” memory clinic team setting for ADRD patients. As the number of HCPs working in team settings continues to grow in Canada, it is important to look at the experiences of these teams to understand the rewards, challenges and motivations of team members. Conclusions: These findings provide more context in understanding how to motivate future HCPs to work with more complex populations such as ADRD patients. Future research should address the outcomes of these clinics by exploring patient and family caregiver experiences with specialized teams, as it is important to gain their experiences to enhance the care practices for these individuals.
Keywords: Alzheimer's Disease and Related Dementias (ADRD); Memory Clinics; Health Care Providers; Health Teams; Experiences; Health Studies and Gerontology